Analyzing the Proposals of FAP 8B Project of Dhaka and Present Context of Retention Pond Areas and Canals - Bivash Das; Ishrat Islam (Journal of Bangladesh Institute of Planners, 2010)
After the devastating flood of 1988, the government adopted a program under FAP-8B to protect Dhaka city from flooding. It included two-part coordinated action plan, namely FAP-8A & FAP-8B. The project “FAP-8B” covered 136.5 sq. km of western part of Dhaka and the primary objective was to provide a relatively flood free and secured living environment. Proposals of FAP-8B focused on construction of retention ponds with pumping facilities and rehabilitation of 21 major natural canals having a total length of 78.6 km. The FAP-8B project started in 1991 and completed by 1997. This paper studied the land use changes within the designated retention pond areas and canals in the FAP-8B area through interpretation of satellite images and data on physical features. The study used satellite images of the years 1989, 1999, 2004, 2007, RS (Revenue Survey) maps and land use maps of Detailed Area Plan (DAP). Findings of the study revealed that proposed 4.5% retention pond areas of FAP-8B has been encroached by various land use activities and at present only 1.79% retention pond areas are left. Encroachments of natural canals are also alarming. It is found that 34% area of 13 natural canals has been filled up by developers, private individuals and others. Between 1989 and 2007, area of wetland was reduced from 22.15% to 12.17% in the west Dhaka. The results suggest that without government intervention to save the remaining retention areas and canals, it would be difficult to uphold the flood control functions of FAP-8B project. Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 89-102